Optimization ratios and multi factor service adaptability of cement-GGBFS stabilized silt in pavement structures - Zhu, Chenyu; Yang, Dianqiu; Song, Bingquan; Wang, Yujin; Hu, Yunfeng; Wu, Hengzhen (Frontiers in Materials, 2025)
Silt soil is widely distributed in coastal, river, and lacustrine sedimentary zones, characterized by high water content, low bearing capacity, high compressibility, and low permeability, representing a typical bulk solid waste. Studies have shown that cement and ground granulated blast furnace slag (GGBFS) can significantly enhance the strength and durability of stabilized silt. However, potential variations due to groundwater fluctuations, long-term loading, or environmental erosion require further validation. This study comprehensively evaluates cement-slag composite stabilized silt as a sustainable subgrade material through integrated laboratory and field investigations. Laboratory tests analyzed unconfined compressive strength (UCS), seawater erosion resistance, and drying shrinkage characteristics. Field validation involved constructing a test section with embedded sensors to monitor dynamic responses under 50% overloaded truck traffic (simulating 16–33 months of service) and environmental variations. Results indicate that slag incorporation markedly improved the material’s anti-shrinkage performance and short-term erosion resistance. Under coupled heavy traffic loads and natural temperature-humidity fluctuations, the material exhibited standard-compliant dynamic responses, with no observed global damage to the pavement structure or surface fatigue damage under equivalent 16–33-month loading. The research confirms the long-term stability of cement-slag stabilized silt as a subgrade material under complex environmental conditions.